ANALISIS PRAKTIK PERLOMBAAN MEMANCING PERSPEKTIF HUKUM EKONOMI SYARI’AH: (Studi Kasus di Kolam Pancing Selma Dsn. Sedati Ds. Kauman Kec. Ngoro Kab. Jombang) - Amzahril Azis; Syai’in Syai’in (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Amzahril Azis 2025. Analysis of Fishing Competition Practices from the Perspective of Sharia Economic Law (Case Study at Selma Fishing Pond, Sedati Hamlet, Kauman Village, Ngoro District). Thesis, Sharia Economic Law Study Program, Faculty of Islamic Studies, Hasyim Asy’ari Tebuireng University Jombang, Advisor; Syai’in, M.Sy.The author conducted a research titled "An Analysis of Fishing Competition Practices from the Perspective of Sharia Economic Law (Case Study at Selma Fishing Pond, Sedati Hamlet, Kauman Village, Ngoro Sub-district, Jombang Regency)." This study aims to answer two questions: (1) how fishing competitions are conducted at Selma Fishing Pond, and (2) how these practices are viewed from the perspective of Sharia Economic Law.The theoretical framework emphasizes a general overview of competitions in Islam, an overview of fishing competitions, and an overview of Sharia Economic Law. These theories are essential for analyzing the fishing competition practices in accordance with the contracts recognized in Sharia Economic Law.This study examines the fishing competition practices at Selma Fishing Pond in Sedati Hamlet, Kauman Village, Ngoro Sub-district, Jombang Regency, using a Sharia Economic Law perspective. The research employs an empirical juridical approach, using descriptive analysis and relevant documents related to Sharia Economic Law to analyze the fishing competition practices. Selma Fishing Pond is a local recreational destination that provides fishing facilities with both paid and free competition systems. The paid competitions require a participation fee and offer cash prizes and door prizes, while the free competitions are held on special occasions without any fees.This study analyzes the legality of these systems through the lens of Sharia Economic Law, covering aspects such as contracts (akad), and the prevention of gharar (uncertainty) and maysir (gambling). The analysis shows that the paid competition system can be categorized under valid ijarah (rental of facilities) and ju’alah (reward for achievement) contracts in Islamic law, as long as there is clarity of benefits and transparency in fund usage. The direct benefit in the form of fish catch for non-winners also supports the legality of this system.Meanwhile, the free competition system reflects the principles of hibah (gift) and ju’alah, free from gharar and maysir elements, and therefore does not contradict Islamic principles. It also contributes to enhanced social interaction and business sustainability.